2016
DOI: 10.1371/currents.hd.b966ec2eca8e2d89d2bb4d020be4351e
|View full text |Cite|
|
Sign up to set email alerts
|

Thiol-disulfide Oxidoreductases TRX1 and TMX3 Decrease Neuronal Atrophy in a Lentiviral Mouse Model of Huntington’s Disease

Abstract: Huntington's disease (HD) is caused by a trinucleotide CAG repeat in the huntingtin gene (HTT) that results in expression of a polyglutamine-expanded mutant huntingtin protein (mHTT). N-terminal fragments of mHTT accumulate in brain neurons and glia as soluble monomeric and oligomeric species as well as insoluble protein aggregates and drive the disease process. Decreasing mHTT levels in brain provides protection and reversal of disease signs in HD mice making mHTT a prime target for disease modification. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Huntington’s disease (HD) is a progressive autosomal dominant neurodegenerative disorder [ 179 , 180 ] caused by a trinucleotide CAG repeats in exon-1 of the huntingtin gene (HTT) on the fourth chromosome (4p16.3) [ 181 ], resulting in the expression of a polyglutamine-expanded mutant Huntington protein (mHTT) at the amino-terminal end of the protein [ 182 ]. The onset of the disease is typically in early to mid-adult life with a range from childhood to advanced age and is defined by an excess of least 39–42 CAG repeats [ 183 , 184 , 185 ].…”
Section: Huntington’s Diseasementioning
confidence: 99%
“…Huntington’s disease (HD) is a progressive autosomal dominant neurodegenerative disorder [ 179 , 180 ] caused by a trinucleotide CAG repeats in exon-1 of the huntingtin gene (HTT) on the fourth chromosome (4p16.3) [ 181 ], resulting in the expression of a polyglutamine-expanded mutant Huntington protein (mHTT) at the amino-terminal end of the protein [ 182 ]. The onset of the disease is typically in early to mid-adult life with a range from childhood to advanced age and is defined by an excess of least 39–42 CAG repeats [ 183 , 184 , 185 ].…”
Section: Huntington’s Diseasementioning
confidence: 99%
“…The precise role of TMX3 in cells has not been established, yet. Preliminary studies show a protective function of TMX3 against neuronal atrophy in mice models for Huntington's disease [49], a progressive brain disorder caused by an inherited CAG trinucleotide repeat expansion in the huntingtin (HTT) gene [50]. The molecular basis of this protective effect is unclear, also because HTT is a cytosolic protein and a direct interaction with the functional portion of TMX3 can be ruled out.…”
Section: Tmx3 a Classic Pdimentioning
confidence: 99%
“…The molecular basis of this protective effect is unclear, also because HTT is a cytosolic protein and a direct interaction with the functional portion of TMX3 can be ruled out. Since it has been shown that the expression of mutated HTT triggers ER stress, an hypothesis is that TMX3 protects cells against neuronal atrophy mitigating the stress situation [49].…”
Section: Tmx3 a Classic Pdimentioning
confidence: 99%